O protagonismo das atividades educativas influenciando o conhecimento e a prática da autoapalpação das mamas e do exame papanicolau entre estudantes de escolas públicas do período noturno - MENDES, Lorena Campos (2014)
Introduction: Cancer (CA) currently represents a public health problem, once the Information System for Mortality registers that this represents the second cause of death due to illness in Brazil. In this context, and according to data from the National Cancer Institute (INCA) in Brazil, the estimate for the year 2014 points to an occurrence of approximately 567 thousand new cases of neoplasia. Thus, gynecological neoplasia is highlighted as the responsible for more than half of the deaths by CA among Brazilian women, with emphasis on breast and cervical cancer. Under this aspect, educational activities are of great importance as many women, due to their values and culture, do not recognize the measures for prevention and detection of these cancers. Purpose: Verify the efficiency of the educational activity in health carried out with students in high school, Education for Young People and Adults (EJA), and primary teacher training courses in the night period in public schools, concerning Breast Probing (BP) and the Pap Test. Methodological Procedures: It was a practically experimental study of the type before and after. The research was developed with women of 18 years of age or more, students in high school, EJA and primary teacher training courses in the night period in public schools in Uberaba, state of Minas Gerais, making up a total of 20 schools and 540 students. A self-applied instrument was developed, structured with open and closed questions containing socio-demographic and sexual issues as profile information, related to Breast Probing and Pap Tests. Initially, the instrument was applied to the subjects with the intention of verifying their previous knowledge concerning the subject. After this, an educational activity was carried out, concerning Pap Tests and Breast Probing. Immediately after this, the instrument was re-applied to the subjects with the purpose of measuring the knowledge they had acquired and compare it to the previous knowledge. Results: the group was made up of women, mostly between 18 and 29 years of age (63.3%), resident in Uberaba (90.7%), students of EJA (34.1%), carrying out non-paid activities (39.8%), single (46.9%), Internet users (68.0%). Concerning the sexual profile, a great majority declared that they had already had sexual relations (92.6%) and had a sexual partner (76.1%). In a general context, the women showed a higher knowledge deficit related to Breast Probing in comparison to the Pap Test. The question that received the highest proportional rise rate of correct answers, 44.1%, was about who should carry out Breast Probing; another question that called attention was concerning the usefulness of Breast Probing, as the amount of wrong answers was high. Another important factor was related to doing the Pap Test, as 102 (18.9%) women said they had never done the test. Statistic tests showed that there was a rise in knowledge, both in relation to Breast Probing as well as to the Pap Test. Conclusion: The knowledge and practice of Breast Probing and Pap Test is still low among women. However, educational activities showed a positive impact on this knowledge. The need for transmission of information concerning the subject was highlighted, a subject which is of extreme importance to various populations.